Computational fluid dynamic analysis of the exhaust gas flow through absorptive and reactive mufflers: some case studies. (September 2017) - Chatterjee, Sushovan
This paper aims to study comprehensively the flow characteristics of exhaust gases through different types of muffler (e.g. absorptive, reactive and resonating). Geometric models were designed using PRO-E and analysed using ANSYS FLUENT 14. The contours for the pressure, the velocity and the turbulence were plotted for optimization of the muffler design based on the known thermodynamic parameters. On the basis of the variation in these parameters, various hybrid designs were proposed for a muffler and even for a combination of mufflers.